The Influence of Price and Promotion on Purchase Intention in Moderating Consumer Behavior - Diansyah Diansyah; Rinda Utami (Budapest International Research and Critics University, 2022)
The rise of marketing strategies in the business world today makes competition even higher and companies are required to produce a product or service in accordance with the wishes and needs of consumers in order to compete and attract as many consumers as possible. The purpose of this study was to examine the effect of price and promotion on buying interest moderated by consumer behavior. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by SmartPLS 3.0 software. The researcher chose the census technique in the sampling technique, namely all members of the general population in Jabodetabek were used as samples in this study to examine the effect of price and the direct effect of the related variables. The results of this study indicate that price has an effect on buying interest, the effect of promotion on buying interest, the influence of consumer behavior on buying interest, moderation of consumer behavior can strengthen the effect of price on buying interest, moderation of consumer behavior can strengthen the influence of promotion on buying interest. The method of determining the number of respondents' eligibility uses the Hair Method which states that respondents may be 5 to 10 times the number of indicators of research variables.